The Impact Of Work Motivation And Work Discipline On Employee Performance At PT. Aiti Prima Indonesia South Jakarta - Agustin, Irmawati; Sunardi, Didi (Implikasi: Jurnal Manajemen Sumber Daya Manusia, 2024)
The purpose of this study was to determine the effect of Work Motivation and Work Discipline on Employee Performance at PT. Aiti Prima Indonesia South Jakarta. The research method used is a quantitative method. The population and sample amounted to 62 people. The results of the study showed a determination coefficient value of 0.598 or 59.8%. Hypothesis test t count (7.813> 2.000) or sig value 0.000 <0.05, then H0 is accepted and H1 is rejected. Equation Y = 14.131 + 0.649X1, The determination coefficient value is 0.684 or 68.4%. Hypothesis test t count (11.400> 2.000) or sig value 0.000 <0.05, then H0 is accepted and H2 is accepted. Regression equation Y = 10.323 + 0.750X2, The correlation coefficient value of 0.854 means that the independent variable with the dependent variable has a strong relationship level with a determination coefficient of 0.730% or 73.0%. Hypothesis testing obtained the calculated F value> Ftable or (79.702> 3.150). Thus H03 is rejected and Ha3 is accepted, this indicates that there is a significant simultaneous influence between the Influence of Work Motivation and Work Discipline on Employee Performance of PT. Aiti Prima Indonesia South Jakarta.